Polipose nasossinusal - Pitta, Amanda Martins Pereira; Russo , Déborah Ribas; Tonon, Andreza Vire; Yeh, Carolina Oshiro; Oliveira, Gabriela Henrique Bueno de; Silva , Bruna dos Reis Mendes Pereira; Santos, Gustavo Bruno Nascimento; Scombatti , Giovana Camacho; Carvalho, Rafaela Aguiar Rocha de; Drago, Stephanie (Seven Editora, 2024)
Characterized by being a chronic degenerative inflammatory disease of the mucosa, Sinonasal Polyposis is a multiplication of polypoid structures in the nasal cavities and paranasal sinuses, whose pathophysiological mechanisms are still poorly understood in the literature, but which has something in common in all the cases already observed, occurs with the presence of an inflammatory process in the submucosa of the individual. Thus, the main objective of this study was to describe, based on the existing literature, what sinonasal polyposis would be, its characteristics, treatment and challenges of affected individuals. In this sense, the study carried out was a systematic literature review carried out in the first half of 2024 the research used the following descriptors: "Polyposis"; "Chronic Disease"; "Nasal Cavities" in the PUBMED, Scielo and Google Scholar databases, with 10 articles being selected at the end. The results showed that in all cases of patients with sinonasal polyposis there was the presence of an inflammatory condition, however, more studies are needed to have a basis on the disease. DOI:https://doi.org/10.56238/sevened2024.001-038